Epidural analgesia does not influence anastomotic leakage incidence after open colorectal surgery for cancer: A retrospective study on 1, 474 patients. Issue 2 (29th July 2015) - Piccioni, Federico; Mariani, Luigi; Negri, Marta; Casiraghi, Claudia; Belli, Filiberto; Leo, Ermanno; Langer, Martin
<x xml:space="preserve">Abstract</x> Background Anastomotic leakage is a major cause of morbidity after colorectal surgery. Epidural analgesia is the most effective method for postoperative pain relief after major abdominal surgery. Anyhow, its effect on anastomotic leakage rate is still controversial. This study aimed to compare epidural versus intravenous analgesia as risk factor for anastomotic leakage requiring reoperation in patients undergoing open colorectal surgery for cancer. Methods A retrospective study on 1, 474 patients was performed. The Cox proportional hazards model was used to study the relation between primary and secondary factors of risk and anastomotic leakage occurrence within 30 days after elective operation. Results Overall 30‐day anastomotic leakage requiring reoperation was 4.9% (95%CI: 3.8–6.0%). No difference in anastomotic leakage occurrence was observed between the epidural analgesia group and the intravenous analgesia group (Hazard ratio: 0.94; 95%CI: 0.53–1.67%; P = 0.8338). Females had a rate of anastomotic leakage 43% lower than males (P = 0.0301). The diverting stoma resulted to be protective for anastomotic leakage occurrence (P = 0.0052). AL significantly increased postoperative median length of stay but not in‐hospital mortality. Conclusions Epidural analgesia does not influence the AL risk after open colorectal surgery for cancer. J. Surg. Oncol. 2015 111:225–230. © 2015 Wiley Periodicals, Inc.